2020
DOI: 10.3390/ma13071585
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Microstructure Characteristics of Three Different Fine-grained Tailings Sand Samples during Penetration

Abstract: This paper explores the microstructural evolution characteristics of tailings sand samples of different types of infiltration failure during the infiltration failure process. The homemade small infiltration deformation instrument is used to test the infiltration failure characteristics of the tailings sand during the infiltration failure process. Evolutionary characteristics of the internal microstructure pores and particle distribution were also studied. Using CT (computerized tomography) technology to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The paper by [ 21 ] explores the microstructural evolution characteristics of tailings sand samples from different types of infiltration failure during the infiltration failure process. A homemade small infiltration deformation instrument is used to test the infiltration failure characteristics of the tailings sand during the infiltration failure process.…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The paper by [ 21 ] explores the microstructural evolution characteristics of tailings sand samples from different types of infiltration failure during the infiltration failure process. A homemade small infiltration deformation instrument is used to test the infiltration failure characteristics of the tailings sand during the infiltration failure process.…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
“…Microstructure parameters have a certain functional relationship with macro factors. Combining the relationship between macrophysical and mechanical parameters and microstructural parameters, new ideas for future research and the prevention of tailings sand infiltration and failure mechanisms are provided [ 21 ].…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
“…The changes in the mesostructure of the tailings under load cause their macroscopic deformation and destruction as well as changes in the mechanical properties, which are the predominant causes for tailings dam failure [34]. However, the existing studies on the mesoscopic nature of tailings were mainly performed under saturated conditions using physical experiments [35][36][37] or discrete element method (DEM) numerical simulations [38]. Few studies reported the mesostructure evolution of unsaturated tailings particles under load.…”
Section: Introductionmentioning
confidence: 99%